A systems thinking approach: 'the greater push model' for growth and sustainability in Africa - evidence from Ghana. (2015) - Banson, Kwamina E.; Nguyen, Nam C.; Bosch, Ockie J.H.
Over six decades, agricultural policies attempting to increase the competitiveness of project performance had limited success. This is due to the use of traditional project management methods that do not address the complex challenges encountered in a systemic way. This paper provides an example of how a systemic approach is applied to agricultural development. The findings are based on a series of workshops conducted in Ghana in 2013 and 2014. Findings include an established community development model, the 'greater push' and a new way of measuring, monitoring and evaluating sustainable development with Bayesian belief network modelling that satisfies the 'Bellagio principles' for measuring sustainable development indicators. This research contributes to systemic application in project management and can help policy-makers across the world to identify threats to sustainable economic growth and help them to anticipate unintended consequences of their decisions and actions before it is too late to reverse the trend.